PENGEMBANGAN MODEL PENGASUHAN ANAK DALAM KELUARGA UNTUK MEMULIHKAN SISTEM NILAI: Studi Kasus Pada Masyarakat Melayu Sambas. - Supriadi, - (2010)
This dissertation is entitled: The Development of child rearing model in families to Recover the Value System (A Case Study on Melayu Sambas Society). The background of this research was the phenomenon of the low quality of child rearing pattern in families as an impact of a shift in the values of Melayu Sambas Society. Based on this problem, this research formulated the following question: what causes the worrying shift in values among Melayu Sambas Society? The aim of this research is to find a child rearing model in the families of Melayu Sambas Society. The theory referred to in this research in the theories of socialization (Berger, 1993 & Mead, 1972), the theories of social changes (Ogburn, 1986 & Parson, 1986), the theories of child rearing (Hourlock, 1996; Yusuf, 2004; & Ahmad, 2001), the theories of children education (Murdock, 1949; Adiwikarta, 2009; & Rivai, 2004), and the theories of educational values (Djahiri, 1996; Mulyana, 2004;& Winnecof, 1988).This research employed naturalistic method with qualitative research approach. The data were gathered through interview, observation, and documentation studies. The research was located in Sambas Regency, West Kalimantan Province. The subjects of this research were Melayu Sambas Society (community leaders, religious leaders, tribalh chiefs, and head of families) with various social level appropriate with the needs of the research data. The results show that 1) The family value system of Melayu Sambas Society in child rearing pattern gives more emphasis on Islamic education; 2) the shift in the original values of Melayu Sambas Society has occurred for a long time, including the conflict with the ethnic of Madura. This shift in values is marked with the shift in Melayu Sambas Society's life orientation where economic problem becomes the focus and goal of life. 3) The factors causing a shift in the value system of the society eventually leads into economic problems. In addition, the low levels of education and health, poverty, the weak child rearing method in families, the lack of religious education, the weak society leadership, the weak parents and community leaders exemplary, the lack of conducive environment to implement the values, and the weak local culture adhesiveness also contribute to the shift in values of the society; 4) The appropriate education concept to improve the value system of the society in the lifelong education concept by integrating informal education (families) along with its diversity and the formal eduation; and 5) The appropriate strategy to improve the value system of the society is by implementing a disciplinary lifestyle both in the families and in the society and also administering education for prospective parents and parents. In conclusion, family education is necessary to be developed in the society, since it plays a role in the individual and societal life. Family education is a medium of socialization, inheritance, and cultural maintenance for the new generation and also a medium of basic character building for nationalism and love for the country. Further, it is also a medium to prepare the young generation to become parts of society and informal teachers (in their families) for their future families.